Non-Communicable Disease Risk Factors Across Age Groups in Urban Indonesia: A WHO STEPS-Based Study - Muh. Amri Arfandi; Saefurrohim, Muhamad Zakki; Azka, Arlina; Pakki, Irfansyah Baharuddin; Siswanto, Siswanto; Risva, Risva; Azmiardi, Akhmad (Universitas Mulawarman, 2025)
Non-communicable diseases (NCDs) are a major public health concern, with risk factors increasingly observed among younger populations. To describe and compare behavioral and biological NCD risk factors among adolescents (15–19 years), young adults (20–24 years), and adults (25–59 years) in Samarinda, Indonesia. A cross-sectional study was conducted among 242 respondents using the WHO STEPS questionnaire, covering behavioral factors (tobacco, alcohol, physical activity, diet) and biological factors (BMI, blood pressure, blood glucose, cholesterol). Smoking was highest among young adults (22.2%) versus adolescents (9.3%) and adults (17.7%). Adolescents reported relatively higher alcohol use (12.4%). Young adults showed more sedentary behavior (40%). Fruit consumption was inadequate across all groups. Overweight/obesity prevalence increased with age: adolescents (19.4%), young adults (24.4%), adults (54.4%). Adults showed higher hypertension (44.1%) and high cholesterol (35.3%). Behavioral risks emerge during adolescence, while biological risks accumulate with age. Early prevention targeting youth through community-based education and health monitoring is essential.